Microwave Assisted Synthesis of Heterocycles Accompanied by Antimicrobial Screening: Exploring a solvent-free method for microwave-assisted synthesis of Bis-chalcones and Pyrazoles accompanied by antimicrobial screening (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A clean, efficient and solvent free method for the synthesis of Bis-chalcones and Pyrazoles were carried out with the help microwave irradiations and neutral alumina. The novel class of Bis Chalcones and pyrazoles were comprehended by treatment of N-phenyl succinimides with p-fluoro benzaldehyde. The cyclic imide on condensation with p-fluoro benzaldehyde furnished a series of bis chalcones and further they undergo cyclisation with hydrazine hydrate to furnish pyrazoles. This condensation could make better and easier by solvent free mechanism with the help of microwave irradiations and neutral alumina. This method furnished various advantages, such as straight forward work-up procedure, environmentally benevolent, neutral condition and high yield. All the synthesized moieties were characterized and interpreted for antimicrobial activities.